2019
DOI: 10.1002/jemt.23256
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and mechanical properties of the dorsal bony plates in the Chinese sturgeon (Acipenser sinensis)

Abstract: The morphology, composition, and mechanical properties of the dorsal bony plates in the Chinese sturgeon (Acipenser sinensis) were determined in this study. Scanning electron microscopy images of the bony plates revealed a ridge-like shape similar to that of traditional Chinese architecture and displayed hierarchical microstructures whose the degree of mineralization decreased from the surface layer to the internal layer. Moreover, the crests in the central part of the bony plates displayed porous characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Figure 2 presents the morphological characteristics of the Chinese sturgeon and the structural morphology of its ventral bony plates. It should be noted that the ventral bony plates are covered by the fish skin epidermis [ 28 ]. The arrangement characteristics of the ventral bony plates were observed under ultraviolet light ( Figure 2 c), and the results revealed that the bony plates exhibited a ridge-like shape.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 presents the morphological characteristics of the Chinese sturgeon and the structural morphology of its ventral bony plates. It should be noted that the ventral bony plates are covered by the fish skin epidermis [ 28 ]. The arrangement characteristics of the ventral bony plates were observed under ultraviolet light ( Figure 2 c), and the results revealed that the bony plates exhibited a ridge-like shape.…”
Section: Resultsmentioning
confidence: 99%
“…Developed to characterize the mechanical properties of non‐homogeneous, or nanostructured materials at the nanoscale (Wornyo, Gall, Yang, & King, 2007), the nanoindentation technique has been widely used for the measurement of the material properties of polymers (Dominguez et al, 2012; Salerno, Dante, Patra, & Diaspro, 2010; Samadi‐Dooki, Malekmotiei, & Voyiadjis, 2016), ceramics (Gao & Mäder, 2002), biological samples (Chen, Cui, & Chen, 2021; X. Li & Guo, 2019; Oyen, 2015; Sarialioglu Gungor & Donmez, 2021; Yang et al, 2019; Zheng, Guo, Li, & Ma, 2019), metallic alloys (L. Li, Guo, Xu, Li, & Han, 2017; X. Zhou, Jiang, Wang, & Yu, 2008), natural products (Kawasaki et al, 2017; Torres‐Torres, Torres, & García‐García, 2019), and composites (Nagasaki, Ishikawa, Ito, Saito, & Iijima, 2021; Young, Crocker, Broughton, Ogin, & Smith, 2013). Following the use of the method proposed by Oliver and Pharr (Oliver, 1992) for viscoelastic behavior, nanoindentation tests have been applied for the mechanical tests and characterization of single fibers (Wang et al, 2014; Yu, Wang, Lu, Tian, & Lin, 2014), polymer thin‐films (Ago, Jakes, & Rojas, 2013; Francius et al, 2006; Morozov, 2021; Park, Frihart, Yu, & Singh, 2013; Vlad‐Cristea, Riedl, Blanchet, & Jimenez‐Pique, 2012), and multi‐phase composite materials (Hardiman, Vaughan, & McCarthy, 2015; Lee, Wang, Pharr, & Xu, 2007; Loubet, Oliver, & Lucas, 2000; Rodríguez, Garrido‐Maneiro, Poza, & Gómez‐del Río, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Developed to characterize the mechanical properties of nonhomogeneous, or nanostructured materials at the nanoscale (Wornyo, Gall, Yang, & King, 2007), the nanoindentation technique has been widely used for the measurement of the material properties of polymers (Dominguez et al, 2012;Salerno, Dante, Patra, & Diaspro, 2010; Samadi-Dooki, Malekmotiei, & Voyiadjis, 2016), ceramics (Gao & Mäder, 2002), biological samples (Chen, Cui, & Chen, 2021; X. Oyen, 2015;Sarialioglu Gungor & Donmez, 2021;Yang et al, 2019;Zheng, Guo, Li, & Ma, 2019), metallic alloys (L. Li, Guo, Xu, Li, & Han, 2017;X. Zhou, Jiang, Wang, & Yu, 2008), natural products (Kawasaki et al, 2017;Torres-Torres, Torres, & García-García, 2019), and composites (Nagasaki, Ishikawa, Ito, Saito, & Iijima, 2021;Young, Crocker, Broughton, Ogin, & Smith, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As a benthic and long-distance migratory fish, Chinese sturgeon has a long life span (almost 40 years) [22][23][24]. The sturgeon often suffers many threats in its migration journey such as predator attacks, mistakenly caught by fishermen or collision with fishing boats [22,25]. However, unlike the majority of other fish species, most parts of the sturgeon fish skin are not covered by bony scales.…”
Section: Introductionmentioning
confidence: 99%